Effect of Distraction on Children's Behavioral Responses to Pain During IV Catheter Insertion - Mahnaz Shoghi; Nooredin Mohammadi; Mahmood Shamshiri; Tahereh Sadeghi (Tehran University of Medical Sciences, 2012)
Background & Aim: Pain is an unpleasant experience related topotential or actual tissue damage. Distraction is an effective technique to control pain. This study aimed to examine the effect of pressing a small soft ball during intravenous catheter insertion on pain related behavioral responses of children.Methods & Materials: A randomized clinical trial study wasconducted in surgical ward of the Qods hospital in Qazvin, Iran in2010. Sixty children aged 4-6 were selected through a simplerandomized sampling method. The children were allocated into twoequal intervention and control groups. Data were collected using theFLACC scale. In the intervention group, children were asked to press a soft ball during IV catheter insertion. The researcher marked theFLACC during the procedure. In the control group, no distraction wasmade during the IV catheter placement. The data were analyzed usingdescriptive statistics, independent-sample t-test, Chi square at P<0.05.Results: There was no significant difference between the two groups in terms of demographic variables including gender, birth order, race, age and type of disease. In the intervention group, none of the children experienced severe pain during IV catheter insertion; and 63.3% of the children had moderate pain. In the control group, 50.0% of children had moderate pain and 23.3% of them experienced severe pain during IV catheter insertion. There was a significant difference in perceived pain between the children of two groups (P<0.001).Conclusion: Distraction is an effective, non-expensive, and easy-toaccess technique to control and reduce pain in children during IVcatheter placement. This study showed that distraction through pressing a soft ball was effective in reducing the behavioral responses of pain in children who underwent IV catheter placement.